Obwody łowieckie po wyroku Trybunału Konstytucyjnego z dnia 10 lipca 2014 roku - Więckowska, Karolina; Suska, Marek (Zoophilologica. Polish Journal of Animal Studies, 2018)
This essay discusses the background and the consequences of the Polish Constitutional Court’s (TK) judgment of 10th July 2014, P 19/13, stating the unconstitutionality of prescription as the basis for establishing and changing borders of hunting zones. As TK has remarked, in the perspective of limitations for real property owners in their entirety, the procedure of establishing and changing borders of hunting zones should ensure participation of these owners. As a result of this judgement a new institution was established in Polish law – the withdrawal of the ground from the hunting zone, which was the effect of the sluggishness of Polish legislator. In this essay, apart from these problems, the authors also discuss the legislative proposals of new regulations of the real property owner’s legal position, including to right to object to execute hunting on his ground.